1D sequential inversion of portable multi‐configuration electromagnetic induction data. Issue 5 (1st July 2016) - Guillemoteau, Julien; Simon, François‐Xavier; Lück, Erika; Tronicke, Jens
ABSTRACT: We present an algorithm that performs sequentially one‐dimensional inversion of subsurface magnetic permeability and electrical conductivity by using multi‐configuration electromagnetic induction sensor data. The presented method is based on the conversion of the in‐phase and out‐of‐phase data into effective magnetic permeability and electrical conductivity of the equivalent homogeneous half‐space. In the case of small‐offset systems, such as portable electromagnetic induction sensors, for which in‐phase and out‐of‐phase data are moderately coupled, the effective half‐space magnetic permeability and electrical conductivity can be inverted sequentially within an iterative scheme. We test and evaluate the proposed inversion strategy using synthetic and field examples. First, we apply it to synthetic data for some highly magnetic environments. Then, the method is tested on real field data acquired in a basaltic environment to image a formation of archaeological interest. These examples demonstrate that a joint interpretation of in‐phase and out‐of‐phase data leads to a better characterisation of the subsurface in magnetic environments such as volcanic areas.